Individual determinants of work attendance: Evidence on the role of personality - Susi Störmer; René Fahr (Institute for the Study of Labor (IZA), 2010)
We investigate the influence of personality as measured by the Big Five personality scale on absenteeism using representative data for Germany. In particular, the 2005 wave of the German Socio-Economic Panel provides detailed information on socio-economic background characteristics along with a Big Five personality scale. Estimates of a Logit model and of count data regression are used to analyze an empirical model based on the theory of hedonic labour market outcomes. These estimates allow us to test hypotheses on the influence of the Big Five personality traits on work attendance. We find clear negative correlations between the probability to be absent and Conscientiousness as well as Agreeableness. We find a strong positive impact of Neuroticism on work attendance decisions in general and clues for a positive impact of Extraversion among men. When looking at the length of absence occurrences the personality dimensions of Neuroticism and Agreeableness are found to significantly influence male absenteeism. Implications of our results are discussed.
Keywords: J20; M12; M51; 330; Absenteeism; Five Factor Model; personality; count data model; Fehlzeit; Persönlichkeitspsychologie; Zähldatenmodell; Schätzung; Deutschland